Implementation of the Yanbu'a Method Based on Play-Based Learning in Strengthening Al-Qur'an Literacy of Students of Madrasah Ibtidaiyah - Unzilah Khomairohtusshiyamah; Maulidatul Adzimah; Siti Nur Aviatun Hasanah; Najiburrohman (Transformative Service Journal, 2026)
This community service activity aims to empower the Qur'an literacy of elementary school students through the application of the Yanbu'a method based on play-based learning. The problem faced by the partners is the low interest in learning and reading skills of students due to conventional and monotonous learning. This community service program is implemented with a participatory approach through learning mentoring, teacher training, and direct application of the Yanbu'a method combined with educational play activities. The implementation method includes initial observation, program planning, implementation of learning activities, and evaluation of activity results. Data were obtained through observation of the learning process, teacher and student reflections, and activity documentation. The results of the community service show that the application of the Yanbu'a method based on play-based learning is able to gradually increase students' enthusiasm, active participation, and Qur'an reading skills. In addition, interactions between teachers and students become more communicative and the learning atmosphere is more enjoyable. This activity makes a positive contribution to improving the quality of Qur'an learning in elementary school and has the potential to become an applicable learning model that can be replicated in the context of Islamic basic educatio.